Application of therapeutic nucleic acids and RNA interference to create products for personalised medicine - I. P. Shilovskiy; G. B. Pasikhov; V. V. Smirnov; I. A. Kofiadi; M. V. Popova; P. A. Strueva; M. R. Khaitov (Биопрепараты: Профилактика, диагностика, лечение, 2024)
INTRODUCTION. Small interfering RNAs (siRNAs) are among the most promising types of therapeutic nucleic acids aiming at the inhibition of pathogenetically relevant gene expression through the RNA interference mechanism. However, the limited bioavailability and immunogenicity of siRNAs and imperfect delivery systems hinder the clinical potential and applicability of siRNA medicinal products.AIM. This study aimed to summarise recent advances in the development of siRNA medicinal products and the corresponding delivery systems, review clinical trial results, and outline future development prospects for these medicinal products.DISCUSSION. This article covers the molecular mechanisms underlying RNA interference, the considerations for siRNA development, and the techniques for effective siRNA delivery. The article dwells upon various systems for nucleic acid delivery to targeted cells. The most promising delivery systems are non-viral systems, including liposomes, exosomes, nanoparticles, polymers, cell-penetrating peptides, and GalNAc ligands. Their main advantages include their ease of complexation with nucleic acids, modification and functionalization potential, favourable safety profile, ability to cross biological barriers, and tropism to target tissues. The article summarises the information that has accumulated over the past few years in clinical trials of siRNA medicinal products for a range of conditions, including metabolic disorders, infections, and cancers, as well as hereditary, ophthalmic, renal, and hepatic diseases. Special attention is paid to siRNA medicinal products undergoing clinical trials (over 10 products) and approved for clinical use (6 products, including MIR 19, the first authorised Russian siRNA medicinal product).CONCLUSION. Ultimately, siRNA medicinal products are a promising tool for personalised medicine, exhibiting therapeutic potential for a wide range of pathological conditions. Further studies of siRNA medicinal products should aim at improving siRNA production technology to increase their bioavailability and half-life period. In addition, these studies should aim at enhancing delivery systems for these products to mitigate toxicity risks and maximise efficacy.